Experimental investigation of the local environment and lattice distortion in refractory medium entropy alloys. (1st April 2022) - Lilensten, Lola; Provost, Karine; Perrière, Loïc; Fonda, Emiliano; Couzinié, Jean-Philippe; Amann, Fabienne; Radtke, Martin; Dirras, Guy; Guillot, Ivan
Abstract: EXAFS analysis of pure elements, binary and ternary equiatomic refractory alloys within the Nb-Zr-Ti-Hf-Ta system is performed at the Nb and Zr K-edges to analyze the evolution of the chemical local environment and the lattice distortion. A good mixing of the elements is found at the atomic scale. For some compounds, a distribution of distances between the central atom and its neighbors suggests a distortion of the structure. Finally, analysis of the Debye-Waller parameters shows some correlation with the lattice distortion parameter δ², and allows to quantify experimentally the static disorder in medium entropy alloys. Graphical abstract: Image, graphical abstract